Соціальні ризики модернізації містоутворюючих галузей економіки (на прикладі підприємств вугільної галузі) - Надрага, В.І. (Економіка промисловості, 2013)
Стаття присвячена аналізу соціальних ризиків модернізації містоутворюючих галузей економіки. Найбільш гостро вони проявляються у процесах реструктуризації підприємств вугільної галузі. У випадку безсистемного закриття шахт населеним пунктам із моногалузевою вугільною спеціалізацією може загрожувати соціальний колапс. На основі аналізу запропоновано можливі шляхи мінімізації соціальних ризиків розвитку монопрофільних поселень. Статья посвящена анализу социальных рисков модернизации градообразующих отраслей экономики. Наибольшее проявление они находят в процессах реструктуризации предприятий угольной отрасли. В случае несистемного закрытия шахт населенным пунктам с моноотраслевой угольной специализацией может угрожать социальный коллапс. Исходя из проведенного анализа предложены возможные пути минимизации социальных рисков монопрофильных поселений. This article analyzes the social risks of modernization of city-forming industries, which have the greatest manifestation in the process of restructuring the coal industry. In the case of non-system closure of coal mines the settlements with single-industry specialization could be threatened with social collapse. The analysis of the dynamics of the coal-mining regions’ demographic indicators suggests that the social environment changes in the period of market reforms have led to a significant deterioration of the structure and quality of human resources. According to the Law of Ukraine "On Social Services", the social risks can be considered as difficult life circumstances that objectively break the normal vital activity, the consequences of which cannot be overcome by a person without assistance. Therefore, in general, the social risks are those that are caused by the social nature of the relationship, and in most cases it is impossible to protect one from them. The author proves that the study of the social risks should proceed along with the study of the interaction of man and society. The main reason of new social problems that arise as a result of the restructuring of the coal industry is badly thought-out actions of state institutions. Thus, 80% reduction in the operating costs of mines subsidizing had been planned by 2014, and their complete termination – by 2016. Even under the condition of full funding the factor of increase of the social risks for man is not taken into account – the accelerated rate of development of the social factors is the cause of the loss of the stabilizing patterns of thinking. If a person is unable to adequately assess the situation, he is not guided by positive social experiences, but he looks for the easiest answers, which often do not meet the moral order, or are outside the law of the state. The dominant social risk of the coal industry reforming is unemployment. Actualization of the risks of unemployment causes poverty, which, according to the most scholars, acts as the most urgent threat to human development. Integration of factors of poverty with single-industry coal communities determines the risks of inheritance of social problems by a new generation: poor families do not have the possibility of providing good education to their children, that’s why the next generation will not be able to compete in the labor market. It means that the children will have the same status of being poor as their parents. This kind of risks inheritance from generation to generation can not only greatly exacerbate social problems of separate segments of the population, but also lead to the depression of certain regions. Thus, the current phase of the coal industry reform should proceed with the need to minimize the risk of human social development. The major direction of the coal industry reform should be the optimization of the region labor market, particularly with the maximum possible preservation of former jobs and their subsequent diversification. Based on the analysis carried out the possible ways to minimize the social risks of single-industry communities are suggested.